Sociaal-cultureel en educatief werk : het beleid in Vlaanderen : een wegwijzer - De Laeter, Dany; De Pauw, Wim; Lemahieu, Tom; Vermeersch, Lode (Mechelen: Wolters Kluwer Belgium, 2008)
"Dany De Laeter, Wim De Pauw, Tom Lemahieu; Lode Vermeersch"